Nutrient Storage in the Perennial Organs of Deciduous Trees and Remobilization in Spring – A Study in Almond (Prunus dulcis) (Mill.) D. A. Webb - Muhammad, Saiful; Sanden, Blake L.; Lampinen, Bruce D.; Smart, David R.; Saa, Sebastian; Shackel, Kenneth A.; Brown, Patrick H. (Frontiers in Plant Science, 2020)
The annual dynamics of whole mature almond tree nutrient remobilization and the accumulation of nutrients in perennial tissues were determined by sequential coring, tissue sampling, nutrient analysis, whole tree excavation and biomass estimation for trees grown under four nitrogen rate treatments 140 kg ha-1 N (N140), 224 kg ha-1 N (N224), 309 kg ha-1 N (N309) and 392 kg ha-1 N (N392) over two years. Whole tree perennial organ N content was greatest in dormancy then declined through bud swell, flowering and fruit set, achieving the lowest total whole tree nutrient content on March 12, (12-14 days after full bloom (DAFB)) coincident with 60-70% leaf expansion. During this period no net increment in whole tree N content (annual plus perennial N) was observed indicating that tree demand for N for bud break, flowering, fruit set and leaf out was met by remobilized stored N with no net N uptake from soil. Remobilizable N increased with increasing N application up to N309 and was maximal at 44.4±4 kg ha-1 and 37.5±5.7 kg ha-1 for the optimally fertilized N309 in 2012 and 2013 respectively. Net increases in perennial organ N (stored N) commenced 41 DAFB and continued through leaf abscission at 249 DAFB. Total annual N increment in perennial organs varied from 25 to 60 kg ha-1 and was strongly influenced by N rate and tree yield. N remobilized from senescing leaves contributed from 11 to 15.5±0.6 kg ha-1 to perennial stored N. Similar patterns of nutrient remobilization and storage were observed for P, K and S with maximal whole tree perennial storage occurring during dormancy and remobilization of stored P, K, S through to fruit set and 70-100% leaf development. Net annual increment in perennial organ P, K, S commenced 98 DAFB and continued through full leaf abscission at 249 DAFB. Organ specific contribution to remobilizable and stored nutrients changes over the growing season are presented. Details of the pattern of perennial organ nutrient allocation, storage and remobilization provides a framework for the optimal management of nutrients in almond with relevance for other deciduous tree species.